2015
DOI: 10.1186/s12989-015-0104-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a panel of interleukin-8 reporter lung epithelial cell lines to monitor the pro-inflammatory response following zinc oxide nanoparticle exposure under different cell culture conditions

Abstract: BackgroundStably transfected lung epithelial reporter cell lines pose an advantageous alternative to replace complex experimental techniques to monitor the pro-inflammatory response following nanoparticle (NP) exposure. Previously, reporter cell lines have been used under submerged culture conditions, however, their potential usefulness in combination with air-liquid interface (ALI) exposures is currently unknown. Therefore, the aim of the present study was to compare a panel of interleukin-8 promoter (pIL8)-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…Other studies have also compared ALI and submerged conditions with diverging results [17,18,23,25]. Our study can be directly compared to the study performed by Loret et al (2016), which used a very similar approach for toxicity testing the same CeO 2 NPs (NM-212) [17].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Other studies have also compared ALI and submerged conditions with diverging results [17,18,23,25]. Our study can be directly compared to the study performed by Loret et al (2016), which used a very similar approach for toxicity testing the same CeO 2 NPs (NM-212) [17].…”
Section: Discussionmentioning
confidence: 87%
“…These systems have previously been used to generate dry aerosols and expose cultured cells to palladium (Pd) NPs [20], and diesel exhaust particles [21], as well as carbonaceous model (Printex 90) NPs [22]. A general difficulty in comparing different exposure set-ups is the dose comparison [23]. To allow for direct comparisons between these two exposure methods, the cells were cultured at similar conditions (on inserts), and cell doses were analyzed quantitatively (using ICP-MS) and expressed as µg/cm 2 for both ALI and submerged exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the majority of the risk assessment studies on inhaled NPs is performed on submerged monocultures grown on glass or plastic substrates. Several publications have demonstrated that co‐cultures of multiple cell types have a strong influence on the observed cellular responses to inhaled NPs (Blank et al, ; Clift et al, ; Lehmann et al, ; Muller et al, ; Rothen‐Rutishauser, Blank, et al, ; Rothen‐Rutishauser, Mueller, et al, ; Rothen‐Rutishauser et al, ; Stoehr et al, ). Thus, in our case study, four different in vitro models of the lung epithelium were tested in order to quantify whether the in vitro complexity and culturing substrates can affect the detectable pulmonary inflammatory response to AuNPs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, surfactant can be used in the case of lung models (McKenzie et al 2015;Raesch et al 2015) and for oral uptake the different consecutive pH values encountered along the stages of the gastro-intestinal tract can be simulated (Peters et al 2012). Furthermore, skin and lung models may be exposed at the airliquid interface (Stoehr et al 2015) while ingestion models could include a more realistic digestion fluid on one side. Finally, cell models are being refined, and new developments such as microfluidic systems and organoids promise to allow more realistic models and to eliminate the species differences in toxicological data by using human cells (Esch et al 2014;Tralau et al 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%